The teaching of french language in Nigeria: a historical perspective (2015)
The significant value of French language in Nigeria is unquantifiable. Nigeria shares frontiers with many Francophone West African countries and she is also a notable member of many international organizations where she played dominant role. Hence, the diplomatic tie between Nigeria and these francophone countries can be further strengthened with the knowledge of French language. This study however focused attention on the historical analysis of the teaching of French language in Nigeria from the pre-colonial era through the post colonial era with the view to finding a lasting solution to the underdevelopment in the teaching of the language in Nigeria system of education. The incursion of French language into Nigeria system of education dates back to 1878 but not as a core subject. The development in the study of the language did not start until the post colonial era when the need to interact among the independent African states was strongly felt. However, the policy declaration of French language as the second official language in. .'Nigeria in 1997 by General Sanni Abacha, though a welcome development, has not really changed the outlook of the language in Nigeria system of Education. Lack of policy implementation, insensitivity of the government upwards the policy and proliferations of languages on the school curriculum constitute obstacles towards the teaching of French language in Nigeria. It was therefore recommended that government and stakeholders in education should be more alive to their responsibilities in encouraging the teaching and learning of French language across schools in Nigeria.